2019
DOI: 10.1101/830281
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Bocavirus Prevalence In Children With Acute Gastroenteritis From Rural Communities In The Northen Region Of South Africa

Abstract: BACKGROUND: Acute gastroenteritis (AGE) is a leading cause of morbidity and mortality in young children worldwide. Human Bocavirus (HBoV) is an emerging virus globally associated with diarrhea. The aim of this study was to demonstrate the prevalence of HBoV genotypes in children (≤5 years) from rural communities in South Africa (SA) suffering from AGE. MATERIAL AND METHOD:A total of 141 fecal samples of children ≤5 years with acute gastroenteritis (AGE) were collected from rural Primary Health Care facilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
2
0
0
Order By: Relevance
“…We suggest the result of this study may be due to the number of male samples collected is higher than the number of female samples, in addition to the superiority of males over females in terms of physical activity in the stages of breastfeeding and childhood. The distribution of human Bocavirus in the current study showing most infection (55.55%) was observed in infant among age group (6-12) months, following by equal percentage (22.22%) for each age group 0-5 months and 13-24months, while no infection noticed in age group (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).This is in agreement with studies carried out in Egypt [18], India [20], South Africa [24] and Brazil [26]. The higher risks at ages 6-12 months and 13-23 months, may be due to diminish of immunity, as the amount of trance-placental antibodies of the child starts dwindling after 6 months of age in addition could be attributed to the fact that children at these age are either crawling or walking and can easily pick dirt or other contaminated objects for playing or eating [27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We suggest the result of this study may be due to the number of male samples collected is higher than the number of female samples, in addition to the superiority of males over females in terms of physical activity in the stages of breastfeeding and childhood. The distribution of human Bocavirus in the current study showing most infection (55.55%) was observed in infant among age group (6-12) months, following by equal percentage (22.22%) for each age group 0-5 months and 13-24months, while no infection noticed in age group (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).This is in agreement with studies carried out in Egypt [18], India [20], South Africa [24] and Brazil [26]. The higher risks at ages 6-12 months and 13-23 months, may be due to diminish of immunity, as the amount of trance-placental antibodies of the child starts dwindling after 6 months of age in addition could be attributed to the fact that children at these age are either crawling or walking and can easily pick dirt or other contaminated objects for playing or eating [27].…”
Section: Discussionsupporting
confidence: 91%
“…This result agreement with (Alam et al, 2015) in Pakistan [23] and (Sharif et al, 2020) in Bangladesh [21]. While Rikhotso et al, (2019) in South Africa reported that the distribution of HBoV was higher in females than in males [24]. On the other hand (El-Mosallamy et al, 2015) in Egypt [18] and (Mohammadi et al, 2020) in Iran [25] found that the proportion of HBoV positive specimens was equally distributed between the two genders.…”
Section: Discussionsupporting
confidence: 79%